Answer:
Step-by-step explanation:
We know that,
(-)(-) = (+),
(-)(+) = (-),
(+)(-) = (-)
(+)(+)=(+)
Now,
Here, the given expression is,
Hence, Second option is correct.
z = 4
z = -28
z = -112
z = 784
The solution of expression is,
⇒ z = 4
We have to give that,
An expression to solve is,
⇒ 70 = - 7 (- 2 - 2z)
Now, Simplify the expression as,
⇒ 70 = - 7 (- 2 - 2z)
Divide both sides by 7,
⇒ 70/ 7 = - 7 (- 2 - 2z)/7
⇒ 10 = - 1 (- 2 - 2z)
Apply distributive property,
⇒ 10 = 2 + 2z
Subtract 2 on both sides,
⇒ 10 - 2 = 2z
⇒ 2z = 8
Divide on both sides by 2,
⇒ z = 8/2
⇒ z = 4
Therefore, The solution is,
⇒ z = 4
To learn more about the mathematical expression visit:
#SPJ6
6 + 5
-6 + 5
-6 + (-5)
Answer: 6+5
Step-by-step explanation:
Answer:0,2
Step-by-step explanation:
Step-by-step explanation:
2350 million
= 2350 000 000 = 2, 350, 000, 000.